DOI: 10.32657/10356/12053
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of reinforced embankment on soft ground and reliablity analysis

Abstract: Stability analysis of slopes or embankments is greatly affected by uncertainty of soil properties. The current design practice is based on the factor of safety which cannot directly reflect the input uncertainty. Probabilistic stability analysis is a rational way to incorporate uncertainty in the design procedure. Unfortunately, most geotechnical engineers are reluctant to adopt probabilistic techniques. The objective of this study is TABLE OF CONTENTS IV LIST OF TABLES XI LIST OF FIGURES XIII CHAPTER 1 INTROD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 171 publications
(273 reference statements)
0
2
0
Order By: Relevance
“…Slope reliability analyses considering inherent spatial variability of soil properties have attracted considerable research attention in the past few decades (e.g., ). Wang et al have concluded that variation of the most probable slip surface has significant influence on the slope reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Slope reliability analyses considering inherent spatial variability of soil properties have attracted considerable research attention in the past few decades (e.g., ). Wang et al have concluded that variation of the most probable slip surface has significant influence on the slope reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Discretizing the 2-D random fields over the slip surface according to slicesSeveral published works have applied the method of autocorrelated slices directly or indirectly Xu (2006). studied the influence of spatial variation on slope reliability by treating the strength parameters at the mid-point along the base of slices as correlated random variables, and made comparisons with the variance reduction method.…”
mentioning
confidence: 99%